2017
DOI: 10.1007/s00221-017-4931-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced verbal abilities in the congenitally blind

Abstract: Numerous studies have found that congenitally blind individuals have better verbal memory than their normally sighted counterparts. However, it is not known whether this reflects superiority of verbal or memory abilities. In order to distinguish between these possibilities, we tested congenitally blind participants and normally sighted control participants, matched for age and education, on a range of verbal and spatial tasks. Congenitally blind participants were significantly better than sighted controls on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
4
14
0
1
Order By: Relevance
“…Sustained neural activity is a neural correlate of working memory 74,75 , which, in the present study, persisted longer in the blind compared to the sighted model. This phenomenon in the network is consistent with the observation of enhanced verbal working memory performance in congenitally blind individuals compared to control sighted ones 22,[31][32][33] . Note, furthermore, that during the reverberation phase, activity retreats from modality-specific to the modality general association cortices in frontal and temporal cortex (*AT, *PF) in both sighted (time steps [12][13][14] and blind models (time steps [17][18][19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sustained neural activity is a neural correlate of working memory 74,75 , which, in the present study, persisted longer in the blind compared to the sighted model. This phenomenon in the network is consistent with the observation of enhanced verbal working memory performance in congenitally blind individuals compared to control sighted ones 22,[31][32][33] . Note, furthermore, that during the reverberation phase, activity retreats from modality-specific to the modality general association cortices in frontal and temporal cortex (*AT, *PF) in both sighted (time steps [12][13][14] and blind models (time steps [17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…Similar differences in V1 activation have also been reported for single word 27,28 and sentence processing tasks 29,30 , which imply semantic understanding [27][28][29] . Furthermore, congenitally blind people with relatively stronger V1 activity in the processing of meaningful language were reported to show better verbal working memory 22 and generally enhanced verbal abilities compared to sighted individuals 22,[31][32][33] . Although one might argue that visual responses in blind individuals are epiphenomenal with no functional relevance for language processing, a study inducing temporary virtual lesions of the primary visual area (V1) using transcranial magnetic stimulation (TMS) during a verb generation task showed an increase in semantic (but not phonological) errors in blind individuals.…”
Section: Visual Cortex Recruitment During Language Processing In Blinmentioning
confidence: 99%
“…Regarding the working memory data, we observed that blind children outperformed their sighted peers on all the verbal memory tasks (both on the simple and on the complex span tasks). In contrast, the groups did not differ significantly on the spatial task, similarly to what has already been observed with adults (Castronovo & Delvenne, 2013;Dormal et al, 2016;Occelli, Lacey, Stephens, Merabet, & Sathian, 2017). Interestingly, while the sighted showed a larger spatial span when performing the task in their dominant visual modality, there was no difference between the blind tactile span and the sighted visual one.…”
Section: Discussionsupporting
confidence: 81%
“…Congenitally blind adults also show superior performance on some linguistic tasks that recruit the "visual" cortex e.g. verbal memory (Amedi, Raz, Pianka, Malach, & Zohary, 2003;Occelli, Lacey, Stephens, Merabet, & Sathian, 2017;Pasqualotto, Lam, & Proulx, 2013). By contrast, there is at present no evidence for functional relevance of visual cortices to language (or any other cognitive function) in adult-onset blindness.…”
Section: A Sensitive Period In the Neural Substrates Of Language In Bmentioning
confidence: 98%